The Risk of Cardiovascular and Cerebrovascular Disease in Men With a History of Priapism. Issue 1 (9th January 2023) - Mulloy, Evan; Li, Shufeng; Belladelli, Federico; Del Giudice, Francesco; Glover, Frank; Eisenberg, Michael L.
Abstract : Purpose: Priapism is a debilitating condition that affects sexual function. As a majority of cases are idiopathic, investigators have hypothesized underlying vascular dysfunction which may predispose men to priapism. We sought to determine if men are at risk for other sequelae of vascular dysfunction such as cardiovascular and thromboembolic disease after a priapism event. Materials and Methods: Using a large commercial insurance claims data warehouse, we evaluated all men (age ≥20) with a diagnosis of priapism from 2003-2020 and matched them to a cohort of men with other urological disorders of sexual dysfunction (erectile dysfunction, Peyronie's disease, and premature ejaculation). We identified incident disease (cardiovascular disease, heart disease, embolism, thrombosis, cerebrovascular disease) for all cohorts. Results: A total of 10, 459 men with priapism were identified and were matched to men with erectile dysfunction, Peyronie's disease, or premature ejaculation. The mean age was 51.1 years old. Men with priapism showed increased incidence of heart disease, both ischemic (HR 1.24, 95% CI 1.09-1.42) and other heart disease (HR 1.24, 95% CI 1.12-1.38) in the years following the priapism diagnosis. Incident cerebrovascular disease was also more likely in men with a history of priapism (HR 1.33, 95% CI 1.15-1.55). Men requiring treatment for ischemic priapism had a higher hazard of cardiovascular and cerebrovascular disease. In addition, men with more priapism episodes had a higher rate of cardiovascular disease and thromboembolic events. Conclusions: Men with priapism are at increased risk for cardiovascular and cerebrovascular events in the years following a priapism.